Japan’s Reliance on US Extended Nuclear Deterrence: Legality of Use Matters Today - Kimiaki Kawai (Journal for Peace and Nuclear Disarmament, 2022)
Japan declares in its security policy that US extended nuclear deterrence is “essential”. However, policymakers do not seem to have provided sufficient explanation of the legality and the implications of the use of nuclear weapons, even if they argue that the policy of extended nuclear deterrence is essential. From the perspective of international law, three questions can be identified in examining Japan’s reliance on the US extended nuclear deterrence. The first is what the target would be in an anticipated use of nuclear weapons, a question that relates to policymakers’ understanding of nuclear deterrence. The second is whether the civilian population is a permissible target for belligerent reprisals; this question relates to the legality of countervalue strategy targeting an adversary’s cities and civilians as intolerable punishment. The third is whether countermeasures by a third party on behalf of an attacked state are permissible, a question that relates to the legal basis of Japan’s reliance on the US nuclear capabilities. These questions at the nexus of politics and law have been neither addressed in depth in deliberations in the National Diet of Japan nor examined sufficiently in scholarly research. This article addresses these questions and considers the legal challenges and the implications today that are inherent in Japan’s security policy, which relies on US extended nuclear deterrence.